Everyday Matters in Global Private Security Supply Chains: A Feminist Global Political Economy Perspective on Gurkhas in Private Security. Issue 6 (1st November 2016) - Chisholm, Amanda; Stachowitsch, Saskia
Abstract: In a case study of Nepalese Gurkhas working for Western private military and security companies (PMSCs), this article develops feminist global political economy understandings of global labour chains by exploring how the 'global market' and the 'everyday' interact in establishing private security as a gendered and racialised project. Current understandings of PMSCs, and global markets at large, tend to depoliticise these global and everyday interactions by conceptualising the 'everyday' as common, mundane, and subsequently banal. Such understandings, we argue, not only conceal the everyday within private security, but also reinforce a conceptual dualism that enables the security industry to function as a gendered and racialised project. To overcome this dualism, this article offers a theoretically informed notion of the everyday that dissolves the hegemonic separation into 'everyday' and 'global' levels of analysis. Drawing upon ethnography, semi-structured interviews, and discourse analysis of PMSCs' websites, the analysis demonstrates how race, gender, and colonial histories constitute global supply chains for the security industry, rest upon and reinforce racialised and gendered migration patterns, and depend upon, as well as shape, the everyday lives and living of Gurkha men and women.